IMPLEMENTASI FUZZY LOGIC PADA SISTEM MONITORING SUHU POMPA AIR - Yoga Alif Kurnia Utama; Dwi Taufik Hidayat; Nicolas Juniarto (Jurnal Informatika Kaputama (JIK), 2021)
Water pump that used for production activities are usually used continuously. It always makes the water pump overheat which will make water pump damage and can cause considerable electrical power losses. This study tries to overcome this problem by creating a temperature monitoring system which will regulate the performance of the water pump. If overheat is detected (>40oC). Water pump performance regulation is carried out by limiting the water input to the pump using a tap where the tap opening follows Fuzzy Logic rules. This monitoring system will send pump temperature data to a web that can be monitored directly using an Android phone. The test results show that this system can work well in limiting the water entering the pump according to the Fuzzy Logic rules. From this test, it can be concluded that this monitoring system can be used to prevent overheating that will occur in the water pump.